Sustainable Development of Coal Based Energy (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Topical Collection, “Sustainable Development of Coal-Based Energy: Technology, Environment, Humanities, Economy, and Education”, has successfully curated a significant body of interdisciplinary research critical to navigating the future of coal within a global sustainability framework. The published papers present tangible advancements, including intelligent mining systems, backfilling technologies, and methods for controlling mining-induced strata movement and surface subsidence. A strong emphasis is placed on environmental remediation, featuring studies on water resource utilization, greenhouse gas emission control, and the ecological restoration of mining areas. Furthermore, the collection broadens the conversation to encompass essential economic strategies for carbon capture and the reuse of abandoned mines, as well as the vital social and educational dimensions of a just energy transition. By synthesizing technical innovation with holistic policy and management approaches, this compilation provides a robust knowledge base and offers actionable insights for academics, engineers, and policymakers striving to balance energy security with urgent climate and environmental goals.